Flavonoid Compounds of the Catechin from Wungu (Graptophyllum pictum (L.) Griff) Leaves and the Sun Protecting Factor Value - Masyita Masyita; Endah Sayekti; Nurlina Nurlina (Jurnal Akademika Kimia, 2022)
The flavonoid content in wungu (Graptophyllum pictum (L.) Griff.) leaves has the potential as a sunscreen. The study aims to identify isolates of flavonoid compounds from wungu leaves and determine the SPF value. Steps are followed by extraction, fractionation, phytochemical test, separation by chromatography, identification, and SPF test. Extraction was carried out with methanol, followed by fractionation with n-hexane and dichloromethane. Dichloromethane fraction was chosen to proceed to the separation step because the results of the phytochemical test showed a vigorous color intensity for the content of flavonoids. The isolate (3.6 mg; dark green; amorphous; mp. 132-136 °C) was identified using a UV-Vis spectrophotometer using methanol as a solvent with a shift reagent NaOH, AlCl3, and a mixture of concentrated AlCl3 and HCl. Based on the UV-Vis spectra, the isolate was predicted to be flavonoid compounds belonging to the catechin group, which have a hydroxyl group at positions C-3, C-7, and do not have an ortho-hydroxy group in ring B. The SPF value of the isolate of 2.3244 at 100 ppm was determined in vitro and calculated by the Qian equation. Therefore, isolate was categorized as sunscreens that provided minimal protection